IoT-enabled double-layered security door lock system for enhanced safety - Muhammad Fachrul; Adelhard Rehiara; Pandung Sarungallo (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Conventional mechanical locks are vulnerable to key duplication and manipulation, while existing IoT-based smart locks often lack multi-layer authentication, real-time monitoring, and energy efficiency considerations. Furthermore, energy efficiency considerations in smart lock systems have received limited attention despite their importance for sustainable engineering. These limitations necessitate the development of more robust security architectures that integrate biometric verification with cloud-based access management to enhance system reliability and scalability. Methods: This study implements a dual-layer smart lock system integrating fingerprint authentication (AS608 sensor) with cloud-based remote control via Blynk IoT platform. The system uses Arduino Mega 2560 for local control and Wemos D1 Mini (ESP8266) for cloud communication. Performance was evaluated based on authentication accuracy (FAR/FRR), power consumption, battery endurance, and notification reliability. Findings: The system achieved FAR = 0% and FRR = 2.5% over 40 attempts, with 100% cloud notification delivery under stable Wi-Fi. Power consumption measured 4.5 W (standby) and 15.6 W (active). Battery endurance reached 19.54 hours (standby) and 5.64 hours (continuous active). Total system cost was IDR 753,635, significantly lower than commercial alternatives. Conclusion: The developed prototype successfully integrates biometric authentication with cloud-based monitoring, resulting in a secure, scalable, and energy-efficient access control solution suitable for residential and commercial applications. This research contributes a reproducible engineering blueprint for dual-controller IoT lock systems with explicit energy performance characterization. The system exhibits enhanced reliability, accessibility, and operational efficiency. Novelty/Originality of this article: This research contributes a complete engineering blueprint for dual-layer IoT lock systems with explicit energy performance characterization, component-level power allocation, and cost analysis—features typically absent in existing smart lock literature.